2009
DOI: 10.1080/15472450802644439
|View full text |Cite
|
Sign up to set email alerts
|

Using Bus Probe Data for Analysis of Travel Time Variability

Abstract: The rapid progress of information technology (IT) may provide us with new insights into understanding traffic phenomena, and could help mitigate traffic problems. One of the key applications of IT to traffic and transport analysis is the identification of the location of moving objects using the Global Positioning System (GPS). It is expected that detailed traffic analysis could be carried out using these data. In this article, we first summarize the various applications of probe data in transport analysis. GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 19 publications
0
48
0
Order By: Relevance
“…A similar approach is investigated, utilizing mixtures of normal distributions to estimate mean travel times for arterial routes with Next Generation Simulation (NGSIM) data (Feng et al, 2011). Uno et al (2009) discuss route travel time variability using bus probe data. In pre-processing stage of their method, a map matching procedure and a data filtering for dwell time elimination are performed.…”
Section: Travel Time Estimation Literature Reviewmentioning
confidence: 99%
“…A similar approach is investigated, utilizing mixtures of normal distributions to estimate mean travel times for arterial routes with Next Generation Simulation (NGSIM) data (Feng et al, 2011). Uno et al (2009) discuss route travel time variability using bus probe data. In pre-processing stage of their method, a map matching procedure and a data filtering for dwell time elimination are performed.…”
Section: Travel Time Estimation Literature Reviewmentioning
confidence: 99%
“…The key findings: - Uno et al (2009) suggested investigation of several factors: weather condition, design of road, land use along road, etc. We have also identified the important influencing factors as preliminary hypotheses, and then revealed their effects.…”
Section: Discussionmentioning
confidence: 99%
“…Uno et al (2009) determined the level of service of a certain route by the journey times. Mean values and deviations of the journey times have been considered.…”
Section: Literature Review -Related Workmentioning
confidence: 99%
“…The initial studies used GPS data to estimate travel time from the bus location data 5 . After developing techniques for travel-time estimation from GPS data, historical data were utilized for predicting travel time using artificial neural network and Kalman filter method 6,7 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the travel-time estimation, average commercial speed of the buses was also estimated 8 . After the travel-time estimation and prediction studies, the travel-time variability (TTV) and reliability studies were reported 5,[9][10][11][12] . Day-to-day and period-toperiod travel-time reliability analysis was also carried out earlier 13 .…”
Section: Literature Reviewmentioning
confidence: 99%